Using the Cosmic Curriculum of Dr. Montessori Toward the Development of a Place-Based Indigenous Science Program - Schonleber, Nanette (Journal of Montessori Research, 2021)
Indigenous educators desire to use culturally restorative and decolonized pedagogies reflective of their own cultural values and beliefs in their science programs but have lacked models for how to start. They also often lack confidence in their ability to teach the sciences. This three-year qualitative case study used grounded theory methodology to discover (a) how Hawaiian language immersion (HLC) K–6 educators used Maria Montessori’s Cosmic Curriculum for the creation of a science program based on Hawaiian epistemology and cultural values and (b) why the Cosmic Curriculum appealed to the HLC educators. Five key themes emerged: (a) the notion of creation as interconnected and relational, (b) an epistemological similarity regarding how people learn, (c) using timelines as organizing cognitive structures, (d) a focus on the natural sciences, and (e) the use of storytelling and key lessons to engage students. Participants stated that they felt successful in creating science curriculum and teaching the sciences as they adapted the above aspects of Dr. Montessori’s Cosmic Curriculum. Future research should be conducted to discover if her Cosmic Curriculum can be adapted for use in other types of non-Montessori program and whether this kind of science program could encourage students to choose the sciences as a career choice.